Advertising: An Entity of Business Discourse - Taofeek O Dalamu; Ke Yang (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
This study focused on advertising as an object of business discourse, revealed through grammatical structures and pictorial images in the frameworks. Eight advertisements of beverages and financial institutions were items of the analysis. The Transitivity system of English operated as the concept of processing the texts. Thus, the application of Transitivity informed the calibration of textual frequencies of the string of words in the advertising plates. The researchers observed three perspectives, where advertising elements correlated with business measures. These were: negotiation through communication; conviction to patronise goods and services; and generation of cash, being the pivot of business firms. Budweiser® employed the features of the crown – The king is here, Guinness Gold® utilised glamorous merriment – Savour the flavour, and Coca-Cola® deployed code-mixing – Gbe bottle e!, to negotiate patronisation of goods and services. Skills’ acquisitions, provision of loans, and personal exaltation were subjects, persuading viewers towards consumption in the Zenith®, Goldberg® and Coca-Cola advertisements. Besides, love, culture and religion, illuminated in StanbicIBTC®, UBA®, and Ecobank® were axioms of communications. The thrust of these strategies was to encourage readers to consume the advertised services, which can lead to cash generation for institutions. As a neglect of advertising might be detrimental to business, this study suggested that the propagation of advertisements en mass might heighten business capacities, which could create different grammatical understanding for discourse analysts.